2008
DOI: 10.1007/s00436-008-1224-9
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of G10, a celery (Apium graveolens)-based topical repellent, against mosquitoes (Diptera: Culicidae) in Chiang Mai province, northern Thailand

Abstract: The potential of G10, a celery (Apium graveolens)-based topical product, as a repellent against natural mosquito populations was evaluated in comparison to commercial (Insect Block 28) and standard (25% DEET) repellents in Chiang Mai province, northern Thailand. These repellent products afforded encouragingly excellent personal protection against a broad range of mosquito species belonging to various genera, including Aedes, Anopheles, Armigeres, Culex, and Mansonia. No mosquito bite was observed on the volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
(31 reference statements)
2
6
0
Order By: Relevance
“…Significant protection afforded by AHE, which was the most effective product, compared favorably with that of its essential oil (AEO: 7.0, 6.0-7.5 h) and DEET (6.25, 5.0-6.5 h). These findings corroborated with those of many works, thus indicating that hexane-extracted plant products are one of the best repellents against various mosquito species (Choochote et al 1999;Tuetun et al 2009;Panneerselvam and Murugan 2013;Singh and Mittal 2013). In general, productivity obtained from extraction with different types of solvents depends on the relative polarity of phytochemicals and extracting solvents (Harborne 1984;Mehta 2002).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Significant protection afforded by AHE, which was the most effective product, compared favorably with that of its essential oil (AEO: 7.0, 6.0-7.5 h) and DEET (6.25, 5.0-6.5 h). These findings corroborated with those of many works, thus indicating that hexane-extracted plant products are one of the best repellents against various mosquito species (Choochote et al 1999;Tuetun et al 2009;Panneerselvam and Murugan 2013;Singh and Mittal 2013). In general, productivity obtained from extraction with different types of solvents depends on the relative polarity of phytochemicals and extracting solvents (Harborne 1984;Mehta 2002).…”
Section: Resultssupporting
confidence: 94%
“…However, Sesamum orientale and L. aromatica were recorded herein for the first time as repellents against A. aegypti, with complete protection times of 0.5 and 1.0 h, respectively, while the other effective products were reported previously as having repellency against mosquitoes and other arthropods (Kamalakannan et al 2011;Evergetis et al 2012;Hazarika et al 2012;Mehmood et al 2012;Rehman et al 2014). Furthermore, the highest repellency was established from both A. sinensis products that belong to the family, Umbelliferae (Apiaceae), of which members such as Apium graveolens, Kaempferia galanga, and Ligusticum sinense are endowed with repellent properties (Choochote et al 2007;Tuetun et al 2009;Evergetis et al 2012;Sanghong et al 2014). These findings suggest that the more the research effort, the greater the chance of finding an efficient alternative.…”
Section: Resultsmentioning
confidence: 66%
“…The improved repellency obtained from LHE-NEG, which was prepared in gel formulation, may be attributed to the effect of the gelling agent, Carbopol ® 940, which may conserve persistence of the active ingredient by making the gel-film a tightly coated skin surface. Similar to the study of Tuetun et al [ 34 ], which revealed that repellency against Ae . aegypti , afforded by formulated gels (2–4.5 h) of Apium graveolens , mostly appeared to have higher repellency than formulated solutions (0–3.5 h).…”
Section: Discussionsupporting
confidence: 90%
“…The larvicidal properties of hexane soluble fraction of Apium graveolens seeds -a plant with pleasant aroma-and three isolated compounds (sedanolide, senkyunolide-N, senkyunolide-J) against Aedes aegypti mosquitoes highlighted sedanolide as very active (100% mortality at 50 mgl -1 , Momin & Nair, 2001). As a consequence, a gel containing 5% of the Apium graveolens hexane extract was developed, providing full protection to volunteers from mosquito bites for two hours (Tuetun et al, 2009), while the ethanolic formulations from the same plant also provided protection against Aedes aegypti. Another formulation containing the aforementioned hexane extract and 5% vanillin showed strong repellent activities against different mosquito species (Tuetun et al, 2005, see also Table 1 for details).…”
Section: Literature Review 21 Umbelliferae (Apiaceae) Family: a Sourmentioning
confidence: 99%